2015
DOI: 10.1016/j.jmb.2015.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Key Residues of S. flexneri OmpA Mediate Infection by Bacteriophage Sf6

Abstract: Many viruses, including bacteriophage, have the inherent ability to utilize several types of proteinaceous receptors as an attachment mechanism to infect cells, yet the molecular mechanisms that drive receptor binding have not been elucidated. Using bacteriophage Sf6 and its host, Shigella flexneri, we investigated how Sf6 utilizes outer membrane protein A (OmpA) for infection. Specifically, we identified that surface loops of OmpA mediate Shigella infection. We further characterized which residues in the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
52
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(67 citation statements)
references
References 57 publications
(82 reference statements)
10
52
2
Order By: Relevance
“…The most obvious possible effect that could lead to P22 resistance would be a low O-antigen polysaccharide amount or length, since its synthesis requires the secretion of several periplasmic proteins. In order to determine whether the yajC deletion has an effect on LPS production, we extracted LPS from the parental strain 14028s and the isogenic DyajC mutant and visualized the resulting preparations in silver-stained SDS polyacrylamide electrophoresis gels (Parent et al, 2014;Porcek and Parent, 2015). There was no effect on LPS functionality as measured by in vitro genome ejection caused by purified LPS nor was there any change in the ability of P22 to adsorb to DyajC cells in vivo using phage depletion methods (see Supporting Information Fig.…”
Section: Host Genes That Prolong Host Dna Survival During Phage P22 Imentioning
confidence: 99%
See 1 more Smart Citation
“…The most obvious possible effect that could lead to P22 resistance would be a low O-antigen polysaccharide amount or length, since its synthesis requires the secretion of several periplasmic proteins. In order to determine whether the yajC deletion has an effect on LPS production, we extracted LPS from the parental strain 14028s and the isogenic DyajC mutant and visualized the resulting preparations in silver-stained SDS polyacrylamide electrophoresis gels (Parent et al, 2014;Porcek and Parent, 2015). There was no effect on LPS functionality as measured by in vitro genome ejection caused by purified LPS nor was there any change in the ability of P22 to adsorb to DyajC cells in vivo using phage depletion methods (see Supporting Information Fig.…”
Section: Host Genes That Prolong Host Dna Survival During Phage P22 Imentioning
confidence: 99%
“…In addition to primary receptors, such as LPS, which mediate initial binding of virions to cells, many phages also must recognize a second cell envelope feature, in order to complete DNA delivery (Casjens and Molineux, 2012). Recently, studies with a close relative of P22 identified multiple outer membrane proteins (Omps) that, in addition to O-antigen, are important for mediating phage Sf6 DNA delivery into Shigella flexneri (Parent et al, 2012(Parent et al, , 2014Porcek and Parent, 2015). OmpA and OmpC were identified as critical for attachment after Sf6 virions conclude their initial interactions with the primary LPS receptor (Verma et al, 1991;Clark et al, 1991;Chua et al, 1999).…”
Section: The Inner Membrane Protein Yajc Is Essential For P22 Infectionmentioning
confidence: 99%
“…Hybrid P22 with either an Sf6 tail needle knob or a T4 foldon tail were induced from prophage, and were a gift from Sherwood Casjens (University of Utah). LPS was purified using a kit (Bulldog Bio), and OmpA was purified as described (Parent et al ., 2014; Porcek and Parent, 2015). Each type of virus with final concentration of 10 9 PFU/ml was incubated with LPS (0.25 mg/ml), or OmpA (0.2 mg/ml), or both LPS and OmpA, all in the presence of detergent Triton X-100 [1.06% (w/v)].…”
Section: Methodsmentioning
confidence: 99%
“…Sf6 infection of Shigella flexneri is a two-step process that utilizes both glycans and proteins during infection. First, Sf6 reversibly recognizes and then hydrolyzes LPS via its tailspikes [23,24]. Second, Sf6 interacts irreversibly with a protein receptor to commit to infection [25].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work showed that OmpA surface loops mediate Sf6 infection and confer host range [23]. Individual amino acid substitutions in OmpA loops result in a range of Sf6 infection efficiencies [23].…”
Section: Introductionmentioning
confidence: 99%